Overall Prevalence and Prevalence Compared among Psoriasis Treatments of Onychomycosis in Patients with Nail Psoriasis and Fungal Involvement - Leena Chularojanamontri (2022)
Background. Whether nail psoriasis can increase the risk of onychomycosis is still being debated, and data relating to the prevalence of onychomycosis among psoriasis patients receiving different treatments is limited. Objectives. To investigate the overall prevalence and prevalence compared among psoriasis treatments of onychomycosis in patients with nail psoriasis and fungal involvement. Methods. A prospective study of three groups of nail psoriasis being treated with only topical medication, methotrexate, or biologics (25 patients per group, 150 nails) was conducted at Siriraj Hospital (Bangkok, Thailand) during November 2018 to September 2020. Demographic data, psoriasis severity, and nail psoriasis severity were recorded. The nail most severely affected with psoriasis on each hand was selected for mycological testing. Potassium hydroxide, periodic acid-Schiff stain, and fungal culture were performed. Results. The prevalence of onychomycosis in nail psoriasis was 35.3%. Among the treatment groups, the prevalence of onychomycosis was significantly higher in the methotrexate group than in the topical treatment and biologic treatment groups (p=0.014). Candida spp. was the main causative organism, followed by Trichophyton rubrum. Thumb was most commonly affected (59.3%). The most common abnormality of the nail matrix and the nail bed was pitted nail (71.3%) and onycholysis (91.3%), respectively. Multivariate analysis revealed diabetes, wet-work exposure, and methotrexate treatment to be predictors of onychomycosis. Conclusions. Several factors, including psoriasis treatment, were shown to increase the risk of onychomycosis in nail psoriasis. Further research is needed to determine whether biologic agents, especially interleukin-17 inhibitors, can increase risk of onychomycosis and Candida infection/colonization of the nails.